Optimization of emergency allocation of necessities of life based on fractal perspective - Li, Hong; Zhou, Zhe; Hu, Chuan; Ning, Yumei; Wang, Zihao; Huang, Hua; Tao, Kangsheng (Frontiers in Public Health, 2023)
The supply and reserves of emergency necessities of life are important for emergency management in disaster events. The scope of the necessities of life changes with social development, and their reserves and allocation in sudden disaster events continually face new challenges. This paper applies fractal theory to the emergency distribution network of the necessities of life, considers road destruction and uncertainty in demand at disaster points in emergencies, and constructs a fractal distribution network optimization model with multiple warehouse points, multi-emergency distribution centers, and multi-disaster points. The model aims to minimize the operating costs of a distribution network, including the cost of building emergency reserve points, transportation costs, and penalty costs for lack of demand. Numerical examples verify the feasibility of the model. The model is solved using LINGO software programming, and an optimal distribution path and quantity are obtained.According to the Economists War-Game Pandemic Threat to Global Growth analysis report, the outbreak of the public health emergency of COVID-19, which created a pandemic, may ultimately destroy 1% of global GDP and cost global GDP more than $1.1 trillion (1).In recent years, the number of disasters worldwide has been increasing. For example, on the morning of February 7, 2021, a glacier in the Jamori district of the Indian state of Uttarakhand collapsed, triggering massive flooding that left more than 207 people dead or missing and forced the emergency evacuation of thousands of people from surrounding areas. In June-July 2021, the United States and Canada experienced historic heat and drought. The heat and drought resulted in more than 1,319 deaths in the U.S. and Canada, thousands of people seeking emergency medical treatment for heat-related discomfort and illness, and more than 58 million people affected by the heat and drought.